Organizational, Marketing Resource Profile And Export Performance - Saban, Gluma (2005)
The most common question that has attracted much attention among scholars and practitioners is why some firms perform better while others do not. To probe further, this dissertation is prepared by focusing on the key determinants of exporting firm performance. In spite of numerous literature on this subject, a need remains for investigating the performance of Malaysian exporting manufacturing firms. This study examines two determinants of export success: the organizational resource profile and marketing resource profile of the firm. This research explores the relationships among the firms’ resources, the firms’ external factors and export performance.